Tantangan Dan Efektivitas Dewan Pengawas Syariah Dalam Implementasi Kepatuhan Syariah Pada Perusahaan Asuransi Syariah - Sabikah, Alifah; Kurniawati, Fitri (WELFARE: Journal of Islamic Economics and Finance, 2025)
The Sharia Supervisory Board (DPS) plays a strategic role in ensuring that Islamic insurance products and operations comply with Sharia principles. This article aims to analyze the role of DPS in overseeing and implementing Sharia compliance in Islamic insurance, the challenges faced, and solutions to enhance the effectiveness of supervision. This study employs a descriptive qualitative research method with a literature review approach. The findings indicate that DPS plays a crucial role as a Sharia compliance supervisor and policy controller within an Islamic insurance company. However, challenges remain, such as the lack of competent and independent human resources, which can hinder the optimal implementation of Sharia compliance. Therefore, strengthening regulations and improving competencies are necessary to enhance Sharia compliance within the Islamic insurance industry.